Do Temperature Thresholds Threaten American Farmland? - Emanuele Massetti; Robert Mendelsohn (Fondazione Eni Enrico Mattei (FEEM), 2017)
Estimated Ricardian models have been criticized because they rely on mean temperatures and do not explicitly include extreme temperatures. This paper uses a cross sectional approach to compare a standard quadratic Ricardian model of mean temperature with a fully flexible daily temperature bin model of farmland values in the Eastern United States. The flexible bin model leads to smaller damages from warming than the quadratic mean specification, but the difference is not statistically significant. Although weather panel studies find high temperature events lead to large annual damage, high temperature events have no harmful effect on farmland values. The results are robust to alternative model specifications and data sets.
Keywords: Q1; Q5; 330; Agriculture; Climate Change; Weather; Crop Yields; Ricardian; Threshold